Formulation And Activity Tests of Anti-Acne Toner 70% Ethanol Extract Black Garlic (Allium sativum L.) - Abdul Aziz Setiawan; Sefi Megawati; Ari Yuniarto; Abdulloh (Postgraduate, University of Mataram, 2025)
Black Garlic (BG) is a fermented product of garlic heated at 60-70ᵒC for 14 days. Black garlic has a black color and has an aroma and taste that is not too pungent like garlic. In Black Garlic S-allylcysteine helps the absorption of allicin making metabolism against bacterial infections easier. The purpose of this study was to determine the physical evaluation and antibacterial activity of 70% ethanol extract Black Garlic (EEBG) as well as the optimum concentration of Staphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes. The study used Single Black Garlic (Allium sativum L.) from Lumajang, East Java, fermented for 30 days at a temperature of 70°C and humidity of 90%. Single black garlic extract is formulated in 3 formulas, including formula 1 (0,5% extract), formula 2 (1% extract), formula 3 (1,5% extract), negatif control (base) and Wardah Acnederm Pure Refining Toner as a comparison. Toner were evaluated by organoleptic testing, pH, homogeneity, and antibacterial activity. The physical results of the toner preparation meet the physical quality requirements which include (organoleptic testing, pH, and homogeneity). The results of the antibacterial activity of toner preparations in formula 1 (0,5% extract), formula 2 (1% extract), formula 3 (1,5% extract), and Commercial toner for antibacterial. The conclusion of this study shows that EEBG has promising antibacterial effects and the evaluation of all instant granules has met the specified requirements.